2016
DOI: 10.1007/s10162-016-0577-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vestibular Function and Low Bone Mineral Density: Data from the Baltimore Longitudinal Study of Aging

Abstract: Animal studies have demonstrated that experimentally induced vestibular ablation leads to a decrease in bone mineral density, through mechanisms mediated by the sympathetic nervous system. Loss of bone mineral density is a common and potentially morbid condition that occurs with aging, and we sought to investigate whether vestibular loss is associated with low bone mineral density in older adults. We evaluated this question in a cross-sectional analysis of data from the Baltimore Longitudinal Study of Aging (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Retrospective studies have found an association between reduced head and to tal BMD, hearing, and balance impairments especially in elderly patients [Kahveci et al, 2014;Mendy et al, 2014]. Further crosssectional studies have reported associa tions between a reduced BMD of the weightbearing hip and lower extremity bones, and gait abnormality evalu ated by the modified Romberg test [Park and Kim, 2016] and saccular dysfunction measured by cVEMPs [Bigelow et al, 2016]. Increasing recent evidence has implicated osteoporosis as a risk factor for BPPV [Byun et al, 2019;Jang and Kang, 2009;Jeong et al, 2009;Parham et al, 2013;Vibert et al, 2003], its recurrence [Byun et al, 2019;Chan et al, De Stefano et al, 2014;Yamanaka et al, 2013], and treatment failure [Jang and Kang, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective studies have found an association between reduced head and to tal BMD, hearing, and balance impairments especially in elderly patients [Kahveci et al, 2014;Mendy et al, 2014]. Further crosssectional studies have reported associa tions between a reduced BMD of the weightbearing hip and lower extremity bones, and gait abnormality evalu ated by the modified Romberg test [Park and Kim, 2016] and saccular dysfunction measured by cVEMPs [Bigelow et al, 2016]. Increasing recent evidence has implicated osteoporosis as a risk factor for BPPV [Byun et al, 2019;Jang and Kang, 2009;Jeong et al, 2009;Parham et al, 2013;Vibert et al, 2003], its recurrence [Byun et al, 2019;Chan et al, De Stefano et al, 2014;Yamanaka et al, 2013], and treatment failure [Jang and Kang, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported an association between reduced bone mineral density (BMD), the occurrence and recurrent events of benign paroxysmal positional vertigo (BPPV) [Jeong et al, 2009;Parham et al, 2013;Yamanaka et al, 2013], balance impairment [Mendy et al, 2014;Park and Kim, 2016], and saccular dysfunction [Bigelow et al, 2016]. Detachment of saccular otoconia obstructing the duc tus reuniens has been radiologically demonstrated and theorized as a mechanism for the development of cochle ar hydrops [Hornibrook and Bird, 2017;Yamane et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the vestibular system modulates muscle fiber size and transcription factor expression in rats [14,42]. Clinical studies have reported a relation between benign paroxysmal positional vertigo with the vestibular dysfunction and osteoporosis, high bone turnover, and vitamin D deficiency in patients with osteoporosis [43][44][45]. Taken together, these findings indicate that vestibular system regulates both skeletal muscles and bones.…”
Section: Muscles and Bonesmentioning
confidence: 99%
“…Osteoporosis and osteopenia can occur at any age, especially in postmenopausal women ( Nilas and Christiansen, 1987 ), and may lead to body pain, fractures, hearing loss and balance disorders ( Bigelow et al., 2016 ; Zuniga et al., 2012 ; Burke-Doe et al., 2008 ). A meta-analysis of five studies from different countries found that a decrease in bone mineral density (BMD) or osteoporosis was significantly associated with hearing loss ( Upala et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%